AI-based avatars are changing the way we learn and teach: benefits and challenges - Fink, Maximilian C.; Robinson, Seth A.; Ertl, Bernhard (Frontiers in Education, 2024)
Advancements in the generative AI field have enabled the development of powerful educational avatars. These avatars can, for instance, listen to users’ spoken input, generate an answer utilizing a large-language model, and reply by speaking with a synthetic voice. A theoretical introduction summarizes essential steps in developing AI-based educational avatars and explains how they differ from previously available educational technologies. Moreover, we introduce GPTAvatar, an open-source, state-of-the-art AI-based avatar. We then discuss the benefits of using educational AI-based avatars, which include, among other things, individualized and contextualized instruction. Afterward, we highlight the challenges of using AI-based educational avatars. Major problems concern incorrect and inaccurate information provided, as well as insufficient data protection. In the discussion, we provide an outlook by addressing advances in educational content and educational technology and identifying three crucial open questions for research and practice.